Comparative analysis of the cardiomyocyte differentiation potential of induced pluripotent stem cells reprogrammed from human atrial or ventricular fibroblasts - Wang, Lu; Nguyen, Thanh; Rosa-Garrido, Manuel; Zhou, Yang; Cleveland, David C.; Zhang, Jianyi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: We had shown that cardiomyocytes (CMs) were more efficiently differentiated from human induced pluripotent stem cells (hiPSCs) when the hiPSCs were reprogrammed from cardiac fibroblasts rather than dermal fibroblasts or blood mononuclear cells. Here, we continued to investigate the relationship between somaticcell lineage and hiPSC-CM production by comparing the yield and functional properties of CMs differentiated from iPSCs reprogrammed from human atrial or ventricular cardiac fibroblasts (AiPSC or ViPSC, respectively). Methods: Atrial and ventricular heart tissues were obtained from the same patient, reprogrammed into AiPSCs or ViPSCs, and then differentiated into CMs (AiPSC-CMs or ViPSC-CMs, respectively) via established protocols. Results: The time-course of expression for pluripotency genes (OCT4, NANOG, and SOX2), the early mesodermal marker Brachyury, the cardiac mesodermal markers MESP1 and Gata4, and the cardiovascular progenitor-cell transcription factor NKX2.5 were broadly similar in AiPSC-CMs and ViPSC-CMs during the differentiation protocol. Flow-cytometry analyses of cardiac troponin T expression also indicated that purity of the two differentiated hiPSC-CM populations (AiPSC-CMs: 88.23±4.69%, ViPSC-CMs: 90.25±4.99%) was equivalent. While the field-potential durations were significantly longer in ViPSC-CMs than in AiPSC-CMs, measurements of action potential duration, beat period, spike amplitude, conduction velocity, and peak calcium-transient amplitude did not differ significantly between the two hiPSC-CM populations. Yet, our cardiac-origin iPSC-CM showed higher ADP and conduction velocity than previously reported iPSC-CM derived from non-cardiac tissues. Transcriptomic data comparing iPSC and iPSC-CMs showed similar gene expression profiles between AiPSC-CMs and ViPSC-CMs with significant differences when compared to iPSC-CM derived from other tissues. This analysis also pointed to several genes involved in electrophysiology processes to be responsible for the physiological differences observed between cardiac and non-cardiac-derived cardiomyocytes. Conclusions: AiPSC and ViPSC were differentiated into CMs with equal efficiency. Detected differences in electrophysiological properties, calcium handling activity, and transcription profiles between cardiac and non-cardiac derived cardiomyocytes demonstrated that 1) tissue of origin matters to generate a better-featured iPSC-CMs, 2) the sublocation within the cardiac tissue has marginal effects on the differentiation process.